Sumbangan Haji Daud Bin Haji Omar al-Libadi Bukit Abal dalam Perkembangan Tasawuf di Kelantan - Sa'ari, Che Zarrina (Afkar: Jurnal Akidah dan Pemikiran Islam, 2007)
Since 19th AD century, history of development of Sufism in the state of Kelantan shows the emergence of many famous local Sufis until nowadays. They have not even left a legacy of knowledge and thought through their respective works, but many of them have left centers of Sufi order with full initiative in dispersing the knowledge of Sufism and in carried out the activities of Sufism. Among those Sufis was Haji Daud bin Haji Omar al-Libadi who is known as Haji Daud Bukit Abal. This artikel will discuss an output of study on him that highlights his biodata, his contribution on works and thought and his contribution on the development of Ahmadiyyah order.